Persistence of Left Superior Vena Cava in Patient submitted a Pacemaker Implantation - Bueno, Sara Carneiro Vicente; Lourenço, Arnaldo Duarte (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
The persistence of the left superior vena cava (PLSVC) is the most frequent thoracic venous malformation, however rare, and with a usually accidental diagnosis. Recurringly, its greatest suspicion is realized in the intraoperative act related to a technical difficulty in performing the procedure, even by more experienced professionals. Case report: patient is 77 years old, woman, chagasic, submitted a definitive pacemaker implant, being the diagnosis of persistence left superior vena cava realized during the surgical procedure. The patient did not present intercurrence during the procedure and developed with substantial clinical improvement after the implantation of the electronic cardiac device, and remaining asymptomatic.